2007
DOI: 10.1530/rep-06-0032
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal profile and reproductive performance in lactation deficient (OFA hr/hr) and normal (Sprague–Dawley) female rats

Abstract: Lactation deficiency may have important consequences on infant health, particularly in populations of low socioeconomic status. The OFA hr/hr (OFA) strain of rats, derived from Sprague-Dawley (SD) rats, has deficient lactation and is a good model of lactation failure. We examined the reproductive performance and hormonal profiles in OFA and SD strains to determine the cause(s) of the lactation failure of the OFA strain. We measured hormonal (PRL, GH, gonadotropins, oxytocin, and progesterone) levels by RIA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 55 publications
5
33
0
1
Order By: Relevance
“…As previously described (Valdez et al 2007(Valdez et al , 2012, we found that OFA hr/hr rats showed lower levels of PRL compared with SD rats only during early lactation (day 2 of lactation, L2) (Fig. 1A).…”
Section: Prl Serum Levels and Mg Development During Early Lactationsupporting
confidence: 85%
See 2 more Smart Citations
“…As previously described (Valdez et al 2007(Valdez et al , 2012, we found that OFA hr/hr rats showed lower levels of PRL compared with SD rats only during early lactation (day 2 of lactation, L2) (Fig. 1A).…”
Section: Prl Serum Levels and Mg Development During Early Lactationsupporting
confidence: 85%
“…The aim of this study was to explore the role of PRL in mammary T-cell population during early lactation using the lactation-deficient OFA hr/hr rats as a model (Valdez et al 2007(Valdez et al , 2012. This strain of rats has a large deletion in the desmoglein 4 gene (Bazzi et al 2004) and shows a partial blockade of the sucking stimulus resulting in low circulating PRL level only during early, and not in mid-or late lactation that leads to a severe impairment in lactation (Valdez et al 2007(Valdez et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific evidence overpoweringly indicates that breast feeding confers significant health benefits to mother and child and is the ideal method for feeding and nurturing infants (Mennella and Pepino, 2010) but lactation insufficiency or failure is relatively common among women (Valdez et al, 2007). Oligogalactia or Perceived Insufficient Milk (PIM) is stated as one of the reasons mentioned most often by women throughout the world for the early discontinuation of breast feeding and/or for the introduction of supplementary bottles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in populations with sufficient economic resources, inadequate lactation may have minor consequences on the growth and health of the infant, because adequate substitute nourishment is available. However, in populations of low socioeconomic status, inadequate lactation can lead to severe health problems in the newborn, whereas a full lactation can assure the normal growth and development of the newborn even in situations of deficient availability of nutrients for the general population (Valdez et al, 2007). Moreover, inadequate breast feeding contributes significantly to the high prevalence of malnutrition (Mathur and Dhingra, 2009).…”
Section: Introductionmentioning
confidence: 99%